Evaluasi Pembelajaran pada Tingkat Sekolah Dasar - Magdalena, Ina; Nurchayati, Aan; Abwandi, Danar (Lembaga Yasin AlSys, 2023)
One of the competencies that must be mastered by a teacher is learning evaluation. This competence is in line with the duties and responsibilities of teachers in learning activities, namely evaluations that can be carried out by educators can be in the form of evaluation of learning outcomes and evaluation of learning. The purpose of learning evaluation is to collect information which is used as the basis for knowing the level of progress, development and achievement of student learning, as well as the effectiveness of teacher teaching. Evaluation of learning includes measurement and assessment activities. The ability to evaluate learning is a basic ability that every teacher absolutely must have. In terms, there are several definitions formulated by experts. However, from some of these opinions it can be concluded that in essence evaluation is a systematic and ongoing process to determine the quality (value and meaning) of something (goals, activities, decisions, performance, processes, people, or objects) based on considerations and criteria. certain in order to make a decision. This study uses the library study research method. Namely a series of activities related to library data collection methods, reading, and recording and managing research materials.